Shopping Behavior Webrooming in Fulfilling Individual Needs From A Perspective Self-Determination Theory - Rahma, Resita Septia; Ramdan, Abdi; Mawar Firdausi, Asri Sekar; Alim, Taqdirul (Master of Management Diponegoro University, 2024)
The development of current consumer behavior shows shopping behavior using more than one channel to reduce fog. This study tries to offer a theoretical concept of omnichannel shopping behavior based on self-determination theory to explain what drives and motivates consumers to do webrooming behavior. This study was conducted using a survey method on 206 consumers who had done webrooming behavior using SEM-PLS analysis. Empirical results indicate that the needs of the three individuals with self-determination are proven to be drivers of consumers in doing webrooming behavior. However, unlike the testing of moderation variables, the three self-determination needs do not fully moderate and only product characteristics moderate the relationship between autonomy variables and webrooming behavior